Hydration interactions beyond the first solvation shell in aqueous phenolate solution. Issue 35 (28th August 2020) - Cota, Roberto; Tiwari, Ambuj; Ensing, Bernd; Bakker, Huib J.; Woutersen, Sander
Abstract : We investigate the orientational dynamics of water molecules solvating phenolate ions using ultrafast vibrational spectroscopy and density functional theory-based molecular dynamics simulations. Abstract : We investigate the orientational dynamics of water molecules solvating phenolate ions using ultrafast vibrational spectroscopy and density functional theory-based molecular dynamics simulations. To assess the roles of the hydrophobic and hydrophilic parts of the anion, we also perform experiments and simulations on solutions of phenol. The experiments show that phenolate immobilizes ( τ or > 10 ps) 6.2 ± 0.5 water molecules beyond the first solvation shell of its oxygen atom, whereas phenol immobilizes only ∼2 water molecules, including the water molecules in its first solvation shell. The simulations reproduce the experiments very well, and show that phenolate causes a local ordering of the hydrogen-bond structure that extends beyond the first solvation shell, thus explaining the experimental observations. The comparison with phenol solution shows that the solvation interaction of phenolate beyond its first solvation shell is due to the high charge density of its negatively charged oxygen atom.